High‐Frequency Thermal Fluctuations and Instabilities in the Radiation Belt Environment. Issue 11 (13th November 2018) - Hwang, Junga; Yoon, Peter H.
Abstract: This paper overviews the electrostatic and electromagnetic theories of spontaneous emission in magnetized plasma as they relate to measured electric and magnetic field fluctuations in quiet time radiation belt and ring current region. The pervasively detected high‐frequency fluctuations in the upper‐hybrid frequency range as well as the background low‐frequency range spectral profile in the whistler mode range are explained within the context of the spontaneous emission theory. The quasilinear calculation of loss cone instability is also carried out in order to validate the assumption of spontaneous emission model. It is shown that the saturated wave amplitudes associated with the upper‐hybrid and multiple‐harmonic cyclotron instability are quite low, indicating that the theoretical explanation based upon the assumption of spontaneous emission theory may be adequate for understanding the observed background fluctuations during quiet times. Plain Language Summary: Since hot electrons constitute only a small fraction of the total electron number density in the space plasma, the general thought has been that the upper‐hybrid fluctuations are useful only as a tool for indirectly measuring the cold electron number density. However, the data from the Van Allen Probes showed that upper‐hybrid electrostatic fluctuations pervasively and ubiquitously exist in the radiation belts. From there, we proved that the presence of hot electrons and upper‐hybrid fluctuations are mutually related phenomenon. We believe that it is the high‐frequency electrostatic fluctuations that are constantly emitted and reabsorbed by the hot electrons, which allow these radiation belt electrons to remain inside the outer radiation belt for such a long time. Key Points: Upper‐hybrid emissions in the radiation belt are interpreted in terms of both loss cone instability and spontaneous emission theories For weak loss cone feature super‐hybrid mode instability saturates at low amplitude Quasi‐isotropic electron distribution with weak or no loss cone feature is adequately explained by spontaneous emission theory